Nursing allocation and adverse events/incidents in intensive care units - Gonçalves, Leilane Andrade; Andolhe, Rafaela; Oliveira, Elaine Machado de; Barbosa, Ricardo Luís; Faro, Ana Cristina Mancussi e; Gallotti, Renata Mahfuz Daud; Padilha, Katia Grillo (Revista da Escola de Enfermagem da USP, 2012)
Patient safety is a challenge for the quality in health care system. This study aimed to analyze the appropriateness of the allocation of nursing staff according to the hours of care required by patients and to identify the relationship between this allocation and adverse events/incidents (EA/I). This research was observational, descriptive and prospective, developed in Clinics ICU located in the 4th floor and 6th floor at a university hospital, in São Paulo, Brazil, from 01/11/07 to10/12/07, with 46 patients. In the 4th floor and 6th floor ICU, respectively, 43,3% and 10.3% of allocations were inadequate (p=0.000). There was a difference in the frequency of EA/I between the adequate and inadequate allocation of nursing staff in the 4th floor and 6th floor ICU, p=0.0004 and p=0.000, respectively. It was concluded that the greater the difference between available and required hours of care in nursing allocations, the lower the frequency of EA/I.